National Security Agency in District Gornja Radgona 1945-1950 - Rihtarič, Ivan (Anali PAZU HD, 2022)
Establishing a new political system after the Second World War was the main purpose of the one-party system with the Communist Party of Yugoslavia (CPY) as the sole and leading political party. In order to protect the new social - political system, the CPY had repressive forces: the National Security Agency (UDV), the People's Militia (NM), the People's Defence Corps of Yugoslavia (KNOJ), prosecutor's offices, courts and prisons. At the beginning of 1946, it carried out forceful eviction of the German population in the Apače region and colonized the area with settlers from other parts of Slovenia. For the CPY, the Catholic Church, big farmers and illegal groups were opponents to the new regime. The UDV in particular, with its wide network of over 400 collaborators (informants, agents, close connections), who operated openly and covertly in the district as well as in the Radgona Corner, had the task of detecting and surrendering to the court the real and alleged opponents of the new regime.
Keywords: District Gornja Radgona; National Security Agency; proxy; informants; agents